Unfit for Democracy? Irrational, Rationalizing, and Biologically Predisposed Citizens. Issue 3 (3rd July 2017) - Rosenberg, Shawn
ABSTRACT: Decades of research demonstrate that most people have little knowledge or understanding of politics. Two recent works suggest that this reflects the limits of human cognitive capacity. Rather than being reasoned, political thinking is mostly preconscious, automatic, and recall driven. Consequently, it is vulnerable to contextual cueing, preexisting biases, and biological and genetic predispositions. However, this research is oriented by an inadequate understanding of cognition.